Financial Inclusion, Cultural Capital, and Women's Economic Empowerment Evidence from PNM Mekaar - Tryas Chasbiandani; Gunawan Baharudin; Shinta Budi Astuti (Penerbit Goodwood, 2026)
Purpose: This study examines the influence of local wisdom andparticipation in the Membina Ekonomi Keluarga Sejahtera(Mekaar) program on women’s economic empowerment amongPNM Mekaar beneficiaries in Bogor Regency, Indonesia.Research Methodology: A quantitative explanatory design wasapplied involving 250 active Mekaar participants selectedthrough purposive sampling. Data were collected using structuredquestionnaires with a five-point Likert scale. Multiple linearregression analysis using SPSS version 26 was employed to testthe effects of local wisdom and Mekaar participation. Validity,reliability, and classical assumption tests were conducted toensure data quality.Results: The findings indicate that local wisdom significantlyaffects women’s economic empowerment (? = 0.352; p < 0.001),while Mekaar participation also shows a significant positiveeffect (? = 0.446; p < 0.001). The model explains 62.7% of thevariance (R² = 0.627; Adjusted R² = 0.624), with Mekaarparticipation as the dominant factor.Conclusions: Women’s empowerment is influenced bysociocultural values and financial inclusion, where theirintegration strengthens sustainable empowerment outcomes.Limitations: The study is limited to one region and a cross-sectional design, restricting causal inference and generalization.Contributions: This study integrates cultural capital andmicrofinance perspectives, providing implications forpolicymakers and microfinance institutions in designingempowerment programs.